2021
DOI: 10.3390/pharmaceutics13030395
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes to Augment Dialysis in Preclinical Models: A Structured Review

Abstract: In recent years, a number of groups have been investigating the use of “empty” liposomes with no drug loaded as scavengers both for exogenous intoxicants and endogenous toxic molecules. Preclinical trials have demonstrated that repurposing liposomes to sequester such compounds may prove clinically useful. The use of such “empty” liposomes in the dialysate during dialysis avoids recognition by complement surveillance, allowing high doses of liposomes to be used. The “reach” of dialysis may also be increased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…It may also be possible to reduce solute binding to albumin by changing plasma pH or ionic strength (31,32). We have described adding powdered activated carbon to the dialysate, and others have explored adding liposomes (33,34). A potential advantage of partial regeneration of dialysate by passage through carbon block is that integration into existing dialysis circuits would be relatively simple.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be possible to reduce solute binding to albumin by changing plasma pH or ionic strength (31,32). We have described adding powdered activated carbon to the dialysate, and others have explored adding liposomes (33,34). A potential advantage of partial regeneration of dialysate by passage through carbon block is that integration into existing dialysis circuits would be relatively simple.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown use of empty liposomes (with no encapsulated drug) to passively increase extraction of endogenous toxins, in order to augment dialysis in preclinical models [ 31 ]. These include liposomes with an acidic core for extracting ammonia in hepatic failure, or cationic, linoleic acid-based, or soy-phospholipid-based liposomes for improving removal of protein-bound endogenous toxins in renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…The microfluidic device consists of a Y-junction, known as a staggered herringbone, followed by a staggered mixing region. The staggered herringbone structures induce rapid mixing by chaotic advection [ 30 ]. Channel 1 was loaded with PBS (pH 7.4) or BSA solution in PBS (10 mg/mL) or Myo solution in PBS buffer (0.15 mg/mL), while DSPC:Chol 50:50 ethanol solution was loaded in channel 2 (see Figure 8 b).…”
Section: Methodsmentioning
confidence: 99%